2016
DOI: 10.1007/s12022-016-9436-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Somatostatin Receptor Type 2A and PTEN in Neuroendocrine Neoplasms Is Associated with Tumor Grade but Not with Site of Origin

Abstract: Neuroendocrine neoplasms (NENs) are derived from endocrine cells in various organs and share common morphological features. This study aimed to clarify whether NENs of different organs are comparable at the molecular pathologic level. We retrospectively collected 99 cases of NENs from gastro-entero-pancreatic, lung, and other organs and reclassified these according to identical criteria. Grade, site, and molecular expression profile including NE markers, Ki-67, p53, somatostatin receptor type 2A (SSTR2A), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Collaud and colleagues revealed that, compared with the carcinoids, the high-grade pulmonary NETs tumors presented a stronger loss of PTEN [11]. Wada and colleagues analyzed the PTEN expression in the NETs of multiple organs and found that PTEN immunoreactivity levels were significantly lower in the high-grade NETs subgroup, while p53 expression were significantly higher in the high-grade NETs subgroup, which was entirely consistent with our results in pulmonary NETs [10]. Our data also revealed that, with the elevation of differentiation grade, p53 expression level gradually increased, but PTEN expression level gradually decreased (Table 3).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Collaud and colleagues revealed that, compared with the carcinoids, the high-grade pulmonary NETs tumors presented a stronger loss of PTEN [11]. Wada and colleagues analyzed the PTEN expression in the NETs of multiple organs and found that PTEN immunoreactivity levels were significantly lower in the high-grade NETs subgroup, while p53 expression were significantly higher in the high-grade NETs subgroup, which was entirely consistent with our results in pulmonary NETs [10]. Our data also revealed that, with the elevation of differentiation grade, p53 expression level gradually increased, but PTEN expression level gradually decreased (Table 3).…”
Section: Discussionsupporting
confidence: 87%
“…Besides, CD117 as a transmembrane tyrosine kinase receptor (TKR) was reported to be overexpressed in most of the high-grade NETs, which suggested a potential therapy of Imatinib [8], [9]. Moreover, somatostatin receptor 2A/5 (SSR2A/5) and phosphatase and tensin homolog (PTEN) expression levels, which were predictive of sensitivity to somatostatin analog and mammalian target of rapamycin (mTOR) inhibitor treatment, respectively, were reported significantly decreased with tumor grade progression, regardless of the site of tumors [10], [11]. Therefore, we wondered whether some similar phenomena in the expression of these markers could be discovered in pulmonary NETs.…”
Section: Introductionmentioning
confidence: 99%
“…Five types of SSTRs have been identified. Somatostatin receptor type 2, especially type 2A, is highly expressed in NETs 13 …”
Section: Neuroendocrine Tumormentioning
confidence: 99%
“…Thus, a more detailed characterization of the two antagonists in vivo, as carried out in the perfusion studies (17), should be performed. However, the wide expression of SSTR2 argues against antagonism for this receptor for future pharmacological development since this may influence many systems; importantly, the Sstr2 has been found to be highly expressed in certain types of cancers (48)(49)(50). SSTR5, on the other hand, is much more discretely expressed with particularly high expression levels in the GLP-1 secreting L-cells in the gut, hopefully limiting any untoward side effects.…”
Section: Consistent With the Notion Thatmentioning
confidence: 99%